DIFFERENTIALLY EXPRESSED PROTEIN PROFILES OF BARIO UPLAND AND MR219 LOWLAND RICE CULTIVARS - Nur Ezzati, Hamdin; Hasnain, Hussain; Nikson Chong, Fatt Ming; Azham, Zulkharnain (UMT Press, 2025)
Traditional Sarawak upland rice known as Bario, exhibits different physical traits in height, flowering period, grain size and starch content compared to commercial rice cultivars. These variations may be associated with the differentially expressed proteins in the rice varieties. This study compared the differentially expressed protein profiles of upland and commercial rice cultivars using 2D-PAGE. The proteins were isolated from leave samples using PEG fractionation and quantified using Bradford assay. The Supernatant Fraction (SF) and Pellet Fraction (PF), two distinct protein fractions were visualised through 2-DE gels and analysed using 2-DE software. The 2D-PAGE analysis revealed the differentially expressed protein profiles between the rice varieties in SF and PF, respectively. Upland rice had fewer protein spots on the 2-DE gels than the MR219 rice cultivar. There were 399 protein spots in SF and 506 protein spots in PF were detected. Specifically, 102 and 129 differentially expressed proteins were found in SF and PF, with a p-value ≤ 0.05 and a fold change ≥ 2.0, respectively. From the value, an abundance of proteins was found down-regulated in the upland rice compared to the commercial rice cultivar. These proteins may contribute to the differences in physical characteristics and other biological responses in the diversity of rice.